Functional analysis of the nonvisual opsins melanopsin and vertebrate ancient opsin (VA opsin) in Atlantic salmon (Salmo salar) - Elsaid, Hassan Osman Alhassan (The University of Bergen, 2017)
The role of nonvisual photoreceptors is yet to be elucidated regarding the link to biological function. This study aims to characterise the expression pattern of melanopsin and vertebrate ancient opsin during early developmental stages of Atlantic salmon, and to relate the function of these genes to hatching. Fertilised salmon’s eggs were subjected to different light qualities using LED technology where intensity and spectrum was manipulated. Two light regimes, 24 hours of continuous light (LL) and 14 hours of light:10 hours of darkness (LD) of white light of different intensities, high, medium, and low, beside different light spectrum of the same intensity, deep red, amber, green, blue, royal blue, and ultra violet were used. Continuous dark was used as a control. Eggs were monitored during the study period and hatched eggs recorded. In situ hybridization technique was used to characterise the expression of two nonvisual opsin, the vertebrate ancient opsin (VA) and melanopsin. The results from hatching experiment show that, while continues white light and LD cycles of white light of the medium intensity increase the hatching period (span), LD cycles of the low intensity white light decease it significantly. However, the time to 50% of hatching is significantly increased by LD cycles of green light blue light, and low intensity of white light. The results from the expression experiments has shown that both melanopsin and VA opsin are expressed in the brain of salmon during the early developmental stages. Both were found in the left habenula, thalamus, hindbrain and spinal cord. Moreover, they have been found to be colocalised in several regions in the brain. Furthermore, regional specific neural activation was found in the habenula and hindbrain, where melanopsin and VA opsin are co-localized, upon light stimulation. This indicate direct photoreception in these brain regions already around hatching. The result indicates that, apparently, the hatching process in salmon may be affected by light to some degree, but ...